Review of 31 cases of neonatal gastrointestinal perforations - Ali Almoamin, Haithem H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Despite the recently improved neonatal intensive management, gastrointestinal perforation during the neonatal period is still a major challenge for pediatric surgeons.Objective: To review the effects of different clinical and operative parameters on the mortality of neonatal intestinal perforations.Patients and Methods: A retrospective study was done to 31 cases of neonatal intestinal perforation at the neonatal intensive care unit of Basrah children speciality hospital during the past four and half years (July 2011 to December 2015). Information regarding the age, sex, gestational age, birth weight, clinical examination, x-rays value in diagnosis, causes and sites of perforations, types of operative procedures, and their effects on prognosis are all studied.Results: Males were affected more than females (a ratio of 3.4: 1); birth weight has a significant association with the prognosis (P-value of 0.045). Hirschsprung`s disease was the commonest cause for perforation (29%), followed by necrotizing enterocolitis and jejunoileal atresia (16.1%, each). Idiopathic perforations constituted only 12.9%. Ileum was the commonest site of perforation (58.1%), followed by cecum (16.1%). Stoma creation was the commonest operative procedure performed. Other procedures like, primary anastomosis, and primary peritoneal drainage followed by laparotomy were also used. This study revealed high mortality rate (45.2%). Complications like sepsis, anastomotic leaks, or burst abdomen carried a high risk of death.Conclusions: High mortality rate is encountered, especially for necrotizing enterocolitis. In contrast to other study, Hirschsprung`s disease is the commonest cause of perforation rather than necrotizing enterocolitis. Radiology has a relatively good accuracy in the diagnosis of intestinal perforations, although some cases were discovered intra-operatively. In this series, prompt accurate treatment with stoma creation harbored the best prognostic results; furthermore no benefits obtained from primary peritoneal drainage.